A review of constitutive models for rubber-like materials - Ali, Aidy; Fouladi, Mohammad Hosseini; Sahari, Barkawi (Science Publications, 2010)
Problem statement: This study reviewed the needs of different constitutive models for rubber like material undergone large elastic deformation. The constitutive models are widely used in Finite Element Analysis (FEA) packages for rubber components. Most of the starting point for modeling of various kinds of elastomer is a strain energy function. In order to define the hyperelastic material behavior, stress-strain response is required to determine material parameters in the strain energy potential and also proper selection of rubber elastic material model is the first attention. Conclusion: This review provided a sound basis decision to engineers and manufactures to choose the right model from several constitutive models based on strain energy potential for incompressible and isotropic materials.